2006
DOI: 10.1128/jvi.80.10.5074-5077.2006
|View full text |Cite|
|
Sign up to set email alerts
|

The High-Frequency Major Histocompatibility Complex Class I Allele Mamu-B * 17 Is Associated with Control of Simian Immunodeficiency Virus SIVmac239 Replication

Abstract: Particular HLA alleles are associated with reduced human immunodeficiency virus replication. It has been difficult, however, to characterize the immune correlates of viral control. An analysis of the influence of major histocompatibility complex class I alleles on viral control in 181 simian immunodeficiency virus SIVmac239-infected rhesus macaques revealed that Mamu-B * 17 was associated with a 26-fold reduction in plasma virus concentrations (P < 0.001). Mamu-B * 17 was also enriched 1,000-fold in a group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
303
1
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(320 citation statements)
references
References 14 publications
13
303
1
3
Order By: Relevance
“…These investigations revealed a new association of Mauritian MHC haplotype and susceptibility/resistance to SHIV 89.6P infection. The association of particular MHC alleles with resistance of rhesus macaques to SIV and SHIV infection is well established [38][39][40][41][42][43]. Our results here extend the phenomenon to cynomolgus macaques of Mauritian origin.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…These investigations revealed a new association of Mauritian MHC haplotype and susceptibility/resistance to SHIV 89.6P infection. The association of particular MHC alleles with resistance of rhesus macaques to SIV and SHIV infection is well established [38][39][40][41][42][43]. Our results here extend the phenomenon to cynomolgus macaques of Mauritian origin.…”
Section: Introductionsupporting
confidence: 81%
“…HLA-B*27 and B*57 are associated with delayed AIDS progression, while HLA-B*35 is associated with accelerated AIDS onset [57]. In rhesus macaques, Mamu-B*17 is associated with reduced plasma viremia and slowed disease progression following infection with SIV mac239 [40,42], although by itself it does not guarantee better disease outcome [58]. Mamu-B*08 positive rhesus macaques display reduced chronic phase viremia following SIV mac239 infection, and the allele is overrepresented in elite controllers [38].…”
Section: Discussionmentioning
confidence: 99%
“…An association with slow disease progression has been reported for Mamu-B*17. 25,27 In our study cohort, like in other populations, 24,27 Mamu-B*17 was linked to Mamu-B*2901 (Table 2). This composite B configuration was linked to two different A regions, one of which carried Mamu-A*02.…”
Section: Mhc Class I Haplotypessupporting
confidence: 76%
“…Several studies have shown that single MHC antigens such as Mamu-A*01 and -B*17 are significantly associated with prolonged survival in SIV-infected rhesus macaques. 13,[25][26][27] However, monkeys sharing one or two of these MHC antigens may still exhibit a variable course of disease. 27,28 We therefore assessed the association between Mhc class I haplotypes, rather than single gene variants, and survival time in SIV-infected rhesus macaques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation